A FIQH MUAMALAH REVIEW ON THE UTILIZATION OF PAWNED GOODS BY CREDITORS - Faisal, Farid; Putra, Panji Adam Agus (AL-IQTISHADIYAH : EKONOMI SYARIAH DAN HUKUM EKONOMI SYARIAH, 2025)
The utilization of pawned goods by creditors is a significant issue in the study of fiqh muamalah, particularly regarding the principles of justice and validity in Islamic economic transactions. This study aims to analyze the utilization of pawned goods by creditors from the perspective of fiqh muamalah and assess its compliance with Shariah principles. The research employs a literature review method with a descriptive-analytical approach, examining primary and secondary sources of Islamic law. The findings indicate that in fiqh muamalah, the utilization of pawned goods by creditors is permissible under the condition that the pawner (rahin) grants explicit permission and that the practice does not involve elements of riba or injustice. However, if the utilization occurs without consent or causes harm to the rahin, it contradicts the principle of justice in Islam. This study also highlights the importance of clear and transparent contracts between the parties involved to prevent potential disputes. The research concludes that the practice of utilizing pawned goods requires strict supervision to ensure Shariah compliance and to foster equitable and blessed economic transactions.